Investigation of Panton-Valentine leukocidin gene among Methicillin resistance for Staphylococcus haemolyticus isolates from Cesarean section infections in Al-Basrah governate, Iraq - Ibrahim, Rabeea A.; Almazini, Mohammed A.; Al-Amara, Saad S. M.; Almazini, Amal A. (Scientific Journal of Medical Research, 2024)
Background: The methicillin-resistant (MR) staphylococci are mainly characterized via the presence of the mecA gene that encodes the production of a low-affinity Penicillin-binding protein (PBP) known as(PBP2a). the pvl as a virulence factor of the synergy-menotropic venom virulence. The pvl is a part of family of homeotropic toxin that is composed of two various components and works together on the cellular membrane synergistically. Methods: One hundred and fifty swab samples were collected from women who had cesarean sections at Al-Basrah Teaching Hospital between October 2022 to January 2023. The Vitek®2 system test revealed for identifying growth. Genomic DNA was extracted from S.haemolyticus isolates according to Geneaid kit protocol, the extraction DNA was amplified by using PCR for mecA gene detection using a specific primer approximately (533bp) and amplified the pvl gene detection using detection using specific primer approximately (433bp). Results: From October 2022 to January 2023, one hundred and fifty swab samples were collected. The samples showed 57 (38%) positive bacterial growth, distributed 51(89.5%) Gram-positive bacterial isolates, while 6(10.5%) gram-negative bacterial isolates, by Using the Vitek® 2 system, various bacterial species were identified. Out of 34 Gram -positive bacteria isolates, the most predominate Staphylococcus hemolyticus 28(82.4%). while the Gram negative bacteria isolates included Klebsiella spp 4(66.7%) isolates, , Escherichia coli 2 (33.3%) isolates. out of (n = 34) isolates Staphylococcus spp. were distributed to 28 (82%) S.haemolyticus and 6 (18%) S.aureus isolates were gave positive results for detection of the mec A gene. While out of (n = 34) isolates were divided into 25 (74%) Staphylococcus spp isolates gave a positive result for the detection of the pvl gene, while the 9 (26%) isolates were shown negative results for the detection of the pvl gene Conclusions: Most isolates of S.haemolyticus and S.aureus were producing Methicillin resistance mecA gene and Panton-Valentine leukocidin (pvl) gene